The Hebrew of the Ben Sira Manuscripts from the Genizah - Joosten, J (De Gruyter, 2019)
The Genizah manuscripts of Ben Sira contain a layer of Hebrew writing composed from scratch in the Middle Ages, as well as some phrases created by medieval copyists unfamiliar with the Second Temple Hebrew of their Vorlage. When these secondary elements are sifted out, to the extent they can be, one is left with a text whose language is still remarkably diverse. The present article presents an attempt at categorizing linguistic phenomena characteristic of this variety.